A new flat shell finite element for the linear analysis of thin shell structures - Hamadi, Djamal; Ayoub, Ashraf; Abdelhafid, Ounis (European Journal of Computational Mechanics, 2015)
In this paper, a new rectangular flat shell element denoted ‘ACM_RSBE5’ is presented. The new element is obtained by superposition of the new strain-based membrane element ‘RSBE5’ and the well-known plate bending element ‘ACM’. The element can be used for the analysis of any type of thin shell structures, even if the geometry is irregular. Comparison with other types of shell elements is performed using a series of standard test problems. A correlation study with an experimentally tested aluminium shell is also conducted. The new shell element proved to have a fast rate of convergence and to provide accurate results.